Unesco recommendation on Historic Urban Landscape in the city of Riobamba. Ecuador - Cardet García, Javier (2022)
The research developed had the objective of generating guidelines for the implementation of UNESCO's recommendation on the Historic Urban Landscape-HUH in the first order area of the historic center of the city of Riobamba (Ecuador). For its fulfillment, the minimum units of the landscape were identified, their diagnosis and the determination of the pressures as factors of deterioration, making possible the proposal of a series of guidelines for their conservation, all supported by a theoretical foundation where the main concepts and theories were analyzed, as well as research related to the object of investigation, from a critical posture where their most significant contributions were assumed. Using a qualitative approach methodology, the instruments used in the research were: observation cards, Nara Matrix, cadastral mapping and expert interviews. As a final result, the UNESCO recommendation on the PUH in the first order zone in the historic center of the city of Riobamba was implemented based on a series of guidelines.